Transcriptome and TCR Repertoire Measurements of CXCR3+ T Follicular Helper Cells Within HIV-Infected Human Lymph Nodes - He, Chenfeng; Malone, Michael J.; Wendel, Ben S.; Ma, Ke-Yue; Del Alcazar, Daniel; Weiner, David B.; De Jager, Philip L.; Del Río-Estrada, Perla M.; Ablanedo-Terrazas, Yuria; Reyes-Terán, Gustavo; Su, Laura F.; Jiang, Ning (Frontiers in Immunology, 2022)
Follicular-helper T cells (TFH) are an essential arm of the adaptive immune system. Although TFH were first discovered through their ability to contribute to antibody affinity maturation through co-stimulatory interactions with B cells, new light has been shed on their ability to remain a complex and functionally plastic cell type. Due to a lack sample availability, however, many studies have been limited to characterizing TFH in mice or non-canonical tissue types, such as peripheral blood. Such constraints have resulted in a limited, and sometimes contradictory, understanding of this fundamental cell type. One subset of TFH receiving attention in chronic infection are CXCR3-expressing TFH cells (CXCR3+TFH) due to their abnormal accumulation in secondary lymphoid tissues. Their function and clonal relationship with other TFH subsets in lymphoid tissues during infection, however, remains largely unclear. We thus systematically investigated this and other subsets of TFH within untreated HIV-infected human lymph nodes using Mass CyTOF and a combination of RNA and TCR repertoire sequencing. We show an inflation of the CXCR3+TFH compartment during HIV infection that correlates with a lower HIV burden. Deeper analysis into this population revealed a functional shift of CXCR3+TFH away from germinal center TFH (GC-TFH), including the altered expression of several important transcription factors and cytokines. CXCR3+TFH also upregulated cell migration transcriptional programs and were clonally related to peripheral TFH populations. In combination, these data suggest that CXCR3+TFH have a greater tendency to enter circulation than their CXCR3- counterparts, potentially functioning through distinct modalities that may lead to enhanced defense.